Analysis of the Effect of Temperature on Performance Efficiency in Three Phase Transformers - Nugraha, Yoga Tri; Pangestu, Adam; Wardani, Sumita; Irwanto, Muhammad; Pasaribu, Faisal Irsan; Evalina, Noorly (ELKHA : Jurnal Teknik Elektro, 2025)
Transformers are essential components in electrical power distribution systems, and their performance is significantly influenced by operating temperature. High temperatures can lead to increased power losses, particularly copper losses, which reduce transformer efficiency. This research examines the impact of temperature on the efficiency of three-phase transformers, focusing on copper losses and the role of cooling systems in maintaining optimal performance. Using a combination of Thermovision infrared imaging and MATLAB simulations, this research introduces a novel integrated approach to correlate real-time thermal data with theoretical modeling of transformer losses. Unlike previous research that relies solely on either simulation or temperature sensors, the use of Thermovision provides spatially resolved, non-invasive temperature measurements that validate and enhance the accuracy of MATLAB-based thermal-electrical models. The results reveal that the operational temperature of 52.9 °C, as detected by Thermovision, is within safe limits; however, higher temperatures significantly decrease efficiency. The efficiency drops from 92.8% at 25 °C to 90.4% at 120 °C. The exponential trend in copper losses with temperature rise underscores the critical role of effective cooling and temperature monitoring systems. While the magnetic flux remains constant, maintaining lower operating temperatures is essential to prevent premature damage and extend transformer lifespan. Thermovision results were used to validate the simulations. Despite small discrepancies, the consistent pattern provides confidence that the simulation model is sufficiently accurate for performance prediction.